7-day compared with 10-day antibiotic treatment for febrile urinary tract infections in children: protocol of a randomised controlled trial. Issue 3 (2nd March 2018) - Daniel, Maria; Szajewska, Hania; Pańczyk-Tomaszewska, Małgorzata
Abstract : Introduction: The optimal duration of antibiotic therapy in children with febrile urinary tract infections (UTIs) is still a matter of debate. Current guidelines recommend treating children with febrile UTIs with antimicrobials for 7 to 14 days. We aim to compare the efficacy and safety of 7-day versus 10-day course of oral or sequence therapy (intravenous with a switch to oral) with cefuroxime/cefuroxime axetil for febrile UTIs in children. Methods and analysis: A non-inferiority, double-blind, randomised, controlled trial will be conducted. Two hundred twenty-one patients aged 3 months to 7 years with febrile UTIs (defined as a combination of fever and leucocyturia in urine sediment) will be randomly assigned to a 7-day treatment arm (7 days of cefuroxime/cefuroxime axetil followed by 3 days of blinded placebo) or a 10-day treatment arm (7 days of cefuroxime/cefuroxime axetil followed by 3 days of blinded cefuroxime axetil). The primary outcome measure will be frequencies of recurrence and reinfection of UTI during the 6 months after the intervention. Ethics and dissemination: The Bioethics Committee approved the study protocol. The findings of this trial will be submitted to a peer-reviewed paediatric journal. Abstracts will be submitted to relevant national and international conferences. Date and protocol version identifier: 04/09/2017 Trial registration number: NCT03221504 .